Financial Institutions in the Global Financial Crisis The Role of Financial Derivatives, Bank Capital, and Clearing and Custody Services - Li, Shaofang (Springer Nature Singapore : Imprint: Springer, 2018)
XI, 246 p. 13 illus. in color.